Procrastinación y su relación con la susceptibilidad al castigo y al refuerzo - Guzmán Barrera, María Elena (Universidad Michoacana de San Nicolás de Hidalgo, 2021)
For many people the term procrastination is unknown, nevertheless, in recent years it is being more used and investigated, we can even find more and more books that address the subject. Likewise, there has been an increase in mental health experts who speak about procrastination, such as Dr. Piers Steel, Dr. Joseph Ferrari, Jane B. Burka and Lenora M. Yuen and Dr. Timothy A. Pychyl to name a few. The available research and literature try to explain procrastination from different points of view and from the analysis of procrastination and its relationship with different factors such as physical health, employment issues, finances, school success, among others. For this reason, on this occasion it was chosen to inquire more about this topic and it was decided to find out if there was a correlation with Sensitivity to Punishment and Reward. Thus, this thesis consists of two studies, in study one, the objective was the creation and analysis of the psychometric properties of a scale of Sensitivity to Punishment and Reward, which was of Hispanic origin and in which It will consider the sensitivity to punishment and reinforcement in the short and medium term. The total number of participants was 240, of which 178 were women and 62 men between the ages of 17 and 64, corresponding to educational or labor institutions in the public and private sectors. The exploratory factor analysis provided good results, yielding a KMO of .84 and in the Bartlett test it was significant p <.001. The exploratory factor analysis was performed with Varimax rotation, 60.98% of the variance was explained, therefore, the results are executable according to the theory of Gray (1987).

Para muchas personas el término procrastinación es desconocido, sin embargo, en los últimos años está siendo más utilizado e investigado, inclusive podemos encontrar cada vez más libros que abordan el tema. Así mismo, ha ido en aumento los expertos en salud mental que hablan de la procrastinación, como lo es el caso del Dr. Piers Steel, el Dr.Joseph Ferrari, Jane B. Burka y Lenora M. Yuen y el Dr. Timothy A. Pychyl por mencionar algunos. Las investigaciones y la literatura disponibles tratan de explicar la procrastinación desde distintos puntos de vista y desde el análisis de la procrastinación y su relación con distintos factores como por ejemplo con salud física, cuestiones laborales, finanzas, éxito escolar, entre otros. Por ello, en esta ocasión se eligió indagar más sobre este tema y se optó por averiguar si había una relación con la Susceptibilidad al Castigo y al Refuerzo. Así pues, la presente tesis consta de dos estudios, en el estudio uno, el objetivo fue la creación y el análisis de las propiedades psicométricas de una escala de Susceptiblidad al Castigo y al Refuerzo, que fuera de origen hispano y en la que se contemplara la susceptibilidad al castigo y al refuerzo a corto y mediano plazo. El número total de participantes fue de 240, de los cuales 178 fueron mujeres y 62 hombres entre los 17 y 64 años correspondientes a instituciones educativas o laborales del sector público y privado. El análisis factorial exploratorio proporcionó buenos resultados arrojando un KMO de .84 y la prueba de Bartlett resultó significativa p<.001. Se realizó el análisis factorial exploratorio con rotación Varimax se explicó el 60.98% de la varianza, por lo tanto, los resultantes son factibles de acuerdo a la teoría de Gray (1987).
Facultad de Psicología. Maestría en Psicología
Keywords: info:eu-repo/classification/cti/4; FP-M-2021-0953; Sensibilidad; Castigo; Recompensa; Dilación; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/6438